2020
DOI: 10.7324/jabb.2020.80101
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of chili encoded miRNAs targeting Chili leaf curl begomovirus and its associated satellite

Abstract: Chili leaf curl virus (ChiLCV), a member of the Geminiviridae family (Genus: Begomovirus), is one of the most destructive plant viruses. Micro (mi) RNAs (miRNAs) are the endogenous non-coding small RNAs that play significant roles in plant growth and stress resistance by degrading targeted mRNA or repressing mRNA translation. Computational methods have identified numerous miRNAs in many plant species, whereas there is no report of chili miRNAs targeting essential genes of the ChiLCV genome and associated satel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A lower (more negative) ΔG suggests a stronger and more stable interaction ( Bernhart et al, 2006 ). A complete complementary between miRNA-mRNA sequences leads to cleavage of the targeted mRNA, while partial complementary typically decreases gene expression by suppressing translation of target mRNA ( Mishra et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A lower (more negative) ΔG suggests a stronger and more stable interaction ( Bernhart et al, 2006 ). A complete complementary between miRNA-mRNA sequences leads to cleavage of the targeted mRNA, while partial complementary typically decreases gene expression by suppressing translation of target mRNA ( Mishra et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PTGS strategy of RNAi through dsRNA results in the biogenesis of target-specific 21-24 nt small RNAs which governs begomovirus resistance in transgenic chili plants. Mishra et al ( 2020a ) identified chili miRNAs specific to essential genes of the ChiLCV through computational methods. They have predicted chili-encoded miRNAs targeting CP (V1) and Rep (C1) genes that could be used for silencing against ChiLCV infection.…”
Section: Advanced Methodsmentioning
confidence: 99%
“…The amiRNA approach has been deployed to develop resistance against cotton leaf curl burewala virus (CLCuD) in cotton and jatropha leaf curl gujarat virus (JLCuGV) in tobacco (Swetha et al, 2018;More et al, 2021). Recently, Mishra et al (2020b) predicted potential mir-miRNAs through in silico analysis, and found some with high sequence similarity to the V1 coat protein and C1 (Rep) genes of ChiLCV, which could be used in the future as a target in amiRNA in chilli. These studies help in understanding the viral gene expression and regulation by host miRNAs that could pave a way into design strategies for defense against ChiLCV infection.…”
Section: Gene Silencingmentioning
confidence: 99%